Revitalisasi Ekonomi Budidaya Ikan Lele Kelompok Tani Penyang Karuhei Desa Mantaren I - Alfrid Sentosa; Aston Pakpahan; Betty Karya; Tutik Haryani; Rosmawiah; Marni; Resviya (Prapanca : Jurnal Abdimas, 2022)
The purposes of economic revitalization by means of catfish farming are to improve the welfare of the people of Mantaren Village and provide worker services to the community through community service activities. The approaches used in community service activities are as follows; The First is the community approach. The Second is the general approach. The Third is the project approach. The Fourth is the cooperative approach. The nets approach is participatory approach. The Sixth is the approach to training and visits. The Seventh is the approach of educational institutions. The last is farming system development approach. The implementation of this mentoring program is based on several stages that have been arranged so that it can run smoothly and regularly in its implementation, while the stages are as follows: (1) The farmer group determines the location where the catfish cultivation will be carried out, (2) Then, the farmer Performs land clearing around the pond, ( 3) Afrer that, the farmer Cleans ponds/blocks, (4) then, they give lime/grinding coconut husks or husks to reduce the acid content of peat water, (5) Next, the farmer Inserts catfish seeds, (6) Then, they keep Caring for catfish until they are harvested. The results of the service can be concluded that the assistance carried out is successful because the farmer groups can manage it until the harvest age. Farmer groups need a good management system so that this cultivation can be sustainable and for the Village Government to be able to provide support to farmer groups so that this business can develop again in the future.